DETERMINAN RISIKO KREDIT BANK DENGAN CAR SEBAGAI VARIABEL MODERASI - Irham Lihan; Nurul Husna; Angga Febrian (Universitas Teknokrat Indonesia, 2023)
Risk management in the banking world is a major issue that is often discussed in terms of bank financial stability. One of the risks that is often an important concern in banking is credit risk. In order for banks to be able to exist in operation, play a role in the national economy, and remain at a prime level of health, bank management must be able to pay attention to the related risk aspects. Non-performing loans (NPL) are loans that fall into the category of substandard, doubtful, and bad loans. Non-performing loans (NPLs) greatly affect the soundness of banks. Factors that can affect credit risk include liquidity risk and spread of interest. This study aims to examine the effect of liquidity and spread of interest on bank credit risk with the Capital Adequacy Ratio (CAR) as a moderating variable. The addition of CAR as a moderating variable is intended to strengthen the relationship between the dependent and independent variables. The results of the study show that the Loan to Deposit Ratio (LDR) variable has a significant positive effect on the credit risk (NPL) of commercial banks in Indonesia, the Interest Rate Spread (SIR) variable has a significant positive effect on the Credit Risk (NPL) of commercial banks in Indonesia, and the CAR variable for NPL, it is a moderating homoglezer variable, that is, it is an input NPL variable that is significantly capable of negatively moderating the LDR and SIR variables.Keywords: Credit Risk, Bank Liquidity, Spread of Interest, Capital AdequacyRatio